Perception Against the Activity of Commercial Sex Workers in Slorok Village - Jatmikowati, Sri Hartini (Richtmann Publishing, 2019)
Prostitution has been renowned as social phenomena since ages ago. It becomes a disguised profession under the needs of sexual and social perspective. Prostitution usually occupies a specific area to establish the sex commercial activities to gain more profitable economic benefits. The sex workers and other parties have engaged intensely to defend the existence of prostitution activities and the corresponding area. This study is aimed to identify the perception of commercial sex workers about their professions. It is intended to reveal the motivation and expectation towards their sex activities. The study is conducted in the village of Slorok, Malang East Java, which have known as a prostitution area since the Dutch colonial era. The study applies a qualitative method to analyze the life of a phenomenon of the commercial sex workers especially in the prostitution area where sex activities are concentrated. From the research we found that the main perception of these sex workers emphasize the profession that occupied during a livelihood successfully meets their needs. Although there is a negative stigma from the society upon this profession, the commercial sex workers assume this profession is a self- selected with clear direction and objective which define as an action to survive their living and to meet the needs upon their life expectation.